Terpenoids from the stem bark of Neoboutonia macrocalyx (Euphorbiaceae). (June 2015) - Maffo, Timoleon; Wafo, Pascal; Kamdem, Ramsay Soup Teoua; Melong, Raduis; Uzor, Philip F.; Mkounga, Pierre; Ali, Zulfiqar; Ngadjui, Bonaventure Tchaleu
Graphical abstract: Highlights: Two new secondary metabolites: one new degraded diterpenoid monomer and one new triterpen. Their structures were established by spectroscopic methods, including NMR and MS analyses. Evaluation of the antimicrobial and antifungal activities of extract and the isolated compounds. Abstract: Neoboutomannin A (1 ), a new degraded diterpenoid monomer, and 3α-acetyl-14α-hydroxytaraxan-19, 28-olide (2 ), a new triterpenoid derivative, have been isolated from the stem bark of Neoboutonia macrocalyx Benth (Euphorbiaceae), together with the known compounds, 3-acetyl aleuritolic acid (3 ), 3β-acetoxy oleanolic acid (4 ), oleanolic acid (5 ), 3, 3, 4-tri- O -methylellagic acid (6 ), sitosterol 3- O -β-d -glucopyranoside (7 ) and sitosterol (8 ). Their structures were elucidated on the basis of spectral data and comparison with those present in the literature. The methanol extract of the stem bark of N. macrocalyx showed high toxicity to brine shrimp nauplii (LC50  = 0.6 ± 0.05 μg/mL) and low antifungal activity on Candida albicans and Mucus miehei . Compound 3 exhibited moderate toxicity to brine shrimp (LC50  = 10.0 ± 0.9 μg/mL) and compound 2 showed low antifungal activity.